Effect of KNbO3 on physical and electrical properties of lead-free BaTiO3 ceramic - Pisitpipathsin,N. (Elsevier Limited, 2015)
© 2014 Elsevier Ltd and Techna Group S.r.l. The investigation of the physical and electrical properties of lead-free (1-x)BT-xKN ceramics where x=0.00, 0.03, 0.06, 0.09, 0.12 and 0.15 was carried out. The (1-x)BT-xKN ceramics were prepared by two step mixed oxide method. The ceramic samples were characterized by X-ray diffraction (XRD), micro-hardness testing, scanning electron microscopy (SEM) and electrical measurements. The XRD patterns of (1-x)BT-xKN ceramics revealed change in crystal symmetries from tetragonal to pseudocubic structure with increasing KN contents. The addition of KN contents improved the hardness of the ceramics which 0.85BT-0.15KN composition possesses maximum hardness of 15.24 GPa. Moreover, the addition of KN of x=0.03 enhances the dielectric properties and has a significant effect on grain growth inhibition of the (1-x)BT-xKN ceramics.